2019
DOI: 10.1007/s12079-018-00500-8
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 (MCP-1/CCL2) in diabetic retinopathy: latest evidence and clinical considerations

Abstract: Diabetic retinopathy (DR) is considered as a diabetes-related complication that can render severe visual impairments and is also a risk factor for acquired blindness in both developed as well as developing countries. Through fibrovascular epiretinal membranes (ERMs), this condition can similarly lead to tractional retinal detachment. Laboratory efforts evaluating the DR pathogenesis can be provided by ocular vitreous fluid and ERMs resulting from vitrectomy. The clinical stages of DR are significantly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 110 publications
1
45
1
Order By: Relevance
“…MCP-1 can chemotactically aggregate monocytes, which leads to capillary obstruction, vascular leakage and absence of perfusion. Increased expression of MCP-1 is also implicated in the pathogenesis of DR [27]. Here, we confirmed that LTF suppressed the expression of TNF-α, IL-1β, and MCP-1, which may contribute to the beneficial effects of LTF treatment.…”
Section: Discussionsupporting
confidence: 80%
“…MCP-1 can chemotactically aggregate monocytes, which leads to capillary obstruction, vascular leakage and absence of perfusion. Increased expression of MCP-1 is also implicated in the pathogenesis of DR [27]. Here, we confirmed that LTF suppressed the expression of TNF-α, IL-1β, and MCP-1, which may contribute to the beneficial effects of LTF treatment.…”
Section: Discussionsupporting
confidence: 80%
“…MCP-1 expression has also been detected in eyes with diabetic retinopathy. 18 Likewise, it is known to be involved in the process of developing a fibrotic capsule. 19 Previous research showed that MCP-1 was elevated after cataract surgery for 30 to 90 days, 20 while Inoue et al 21 and Jakobsson et al 11 demonstrated a significant increase of MCP-1 for more than 6 months after cataract surgery in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemoattractant protein-1 attracts and activates monocyte and macrophages (112,113) and stimulates fibrosis and angiogenesis (114). MCP-1 is produced by Müller cells, microglia cells, astrocytes, retinal neurons, ECs, and retinal pigment epithelial cells in patients with diabetes (115). The migration of monocyte into the retina is mediated by MCP-1 coupling to its receptor CCR2 (116).…”
Section: Chemokine: Mcp-1mentioning
confidence: 99%